Radicalization and violent extremism: Perspectives from research on group processes and intergroup relations. (December 2020) - Gøtzsche-Astrup, Oluf; van den Bos, Kees; Hogg, Michael A.
Radicalization and violent extremism leading to violent protests, repression, and terrorist attacks constitute important issues in our world. Social psychological group processes and intergroup dynamics play a key role in creating resilience against or facilitating the path towards violent extremism. The present body of work brings together and furthers our understanding of these factors by integrating insights from other fields, most centrally political science. In this introductory article, we summarize the state of the literature and suggest a social psychological research agenda for studying radicalization and violent extremism. This agenda (a) focuses on how the radicalization process commences and festers in ordinary people; (b) is ambitious in bringing research into the real world with protesters, the repressed, and groups engaged in conflict; (c) is pragmatic in measuring outcomes of interest; and (d) applies field experimental methodology, among other methodologies. With this perspective, we argue, social psychology is ideally positioned for a new decade of impactful research into radicalization and violent extremism.